SARS-CoV-2 Evolution: Implications for Diagnosis, Treatment, Vaccine Effectiveness and Development - Fabrizio Angius; Silvia Puxeddu; Silvio Zaimi; Serena Canton; Sepehr Nematollahzadeh; Andrea Pibiri; Ilenia Delogu; Gualtiero Alvisi; Meng Ling Moi; Aldo Manzin (Vaccines)
The COVID-19 pandemic, driven by the rapid evolution of the SARS-CoV-2 virus, presents ongoing challenges to global public health. SARS-CoV-2 is characterized by rapidly evolving mutations, especially in (but not limited to) the spike protein, complicating predictions about its evolutionary trajectory. These mutations have significantly affected transmissibility, immune evasion, and vaccine efficacy, leading to multiple pandemic waves with over half a billion cases and seven million deaths globally. Despite several strategies, from rapid vaccine development and administration to the design and availability of antivirals, including monoclonal antibodies, already having been employed, the persistent circulation of the virus and the emergence of new variants continue to result in high case numbers and fatalities. In the past four years, immense research efforts have contributed much to our understanding of the viral pathogenesis mechanism, the COVID-19 syndrome, and the host–microbe interactions, leading to the development of effective vaccines, diagnostic tools, and treatments. The focus of this review is to provide a comprehensive analysis of the functional impact of mutations on diagnosis, treatments, and vaccine effectiveness. We further discuss vaccine safety in pregnancy and the implications of hybrid immunity on long-term protection against infection, as well as the latest developments on a pan-coronavirus vaccine and nasal formulations, emphasizing the need for continued surveillance, research, and adaptive public health strategies in response to the ongoing SARS-CoV-2 evolution race.